Developmental differences in amygdala projection neuron activation associated with isolation-driven changes in social preference - Ferrara, Nicole C.; Trask, Sydney; Ritger, Alexandra; Padival, Mallika; Rosenkranz, J. Amiel (Frontiers in Behavioral Neuroscience, 2022)
Adolescence is a developmental period characterized by brain maturation and changes in social engagement. Changes to the social environment influence social behaviors. Memories for social events, including remembering familiar individuals, requires social engagement during encoding. Therefore, existing differences in adult and adolescent social repertoires and environmentally-driven changes in social behavior may impact novel partner preference, associated with social recognition. Several amygdala subregions are sensitive to the social environment and can influence social behavior that is crucial for novelty preference. Amygdala neurons project to the septum and nucleus accumbens (NAc), which are linked to social engagement. Here, we investigated how the social environment impacts age-specific social behaviors during social encoding and its subsequent impact on partner preference. We then examined changes in amygdala-septal and -NAc circuits that accompany these changes. Brief isolation can drive social behavior in both adults and adolescents and was used to increase social engagement during encoding. We found that brief isolation facilitates social interaction in adolescents and adults, and analysis across time revealed that partner discrimination was intact in all groups, but there was a shift in preference within isolated and non-isolated groups. We found that this same isolation preferentially increases basal amygdala (BA) activity relative to other amygdala subregions in adults, but activity among amygdala subregions was similar in adolescents, even when considering conditions (no isolation, isolation). Further, we identify isolation-driven increases in BA-NAc and BA-septal circuits in both adults and adolescents. Together, these results provide evidence for changes in neuronal populations within amygdala subregions and their projections that are sensitive to the social environment that may influence the pattern of social interaction within briefly isolated groups during development.